Hearing screening and cholinesterase activity among rural workers exposed to pesticides - Mattiazzi, Ângela Leusin (Rev Bras Med Trab, 2020)
BACKGROUND: Agricultural activities and exposure to pesticides increase the risk of hearing loss and might reduce cholinesterase activity. OBJECTIVE: To describe and analyze the correlation between hearing screening and plasma and erythrocyte cholinesterase activity relative to rural workers exposed to pesticides. METHODS: Cross-sectional, quantitative, descriptive and explanatory study conducted with 71 rural workers exposed to pesticides. Data were collected by means of an instrument to characterize exposure to pesticides, hearing screening and blood samples to measure plasma and erythrocyte cholinesterase activity. RESULTS: Each participant used three different pesticides, on average, glyphosate being the most frequently mentioned. About 60.6% of the sample exhibited hearing abnormalities and 32.4% complained of tinnitus. Erythrocyte cholinesterase activity was within the normal range in all the cases; one single participant exhibited reduced plasma cholinesterase activity. There was not significant correlation between the hearing screening and cholinesterase levels. CONCLUSION: Audiological evaluation should be included in the assessment of rural workers. Monitoring workers exposed to pesticides should not be restricted to cholinesterase activity alone, because this method is insufficient to detect actual exposure to pesticides.